A Closer Look at Cardioprotective Function of HDL: Revise the HDL – Cholesterol Hypothesis? - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: The strong inverse association of plasma levels of high-density lipoprotein (HDL) cholesterol with coronary heart disease (CHD) found in human epidemiological studies led to the development of the ‘HDL cholesterol hypothesis’, which posits that intervention to raise HDL cholesterol will result in reduced risk of CHD. A number of recent developments have brought the potential protective role of HDL into question. Several clinical trials of agents that substantially raise HDL-C have been demonstrated to not reduce CHD event rates.CONTENT: For decades, HDL and HDL-cholesterol (HDL-C) levels were viewed as synonymous, and modulation of HDL-C levels by drug therapy held great promise for the prevention and treatment of cardiovascular disease. Nevertheless, recent failures of drugs that raise HDL-C to reduce cardiovascular risk and the now greater understanding of the complexity of HDL composition and biology have prompted researchers in the field to redefine HDL. As such, the focus of HDL has now started to shift away from a cholesterol-centric view toward HDL particle number, subclasses, and other alternative metrics of HDL. Many of the recently discovered functions of HDL are, in fact, not strictly conferred by its ability to promote cholesterol flux but by the other molecules it transports, including a diverse set of proteins, small RNAs, hormones, carotenoids, vitamins, and bioactive lipids. Based on HDL’s ability to interact with almost all cells and deliver fat-soluble cargo, HDL has the remarkable capacity to affect a wide variety of endocrine-like systems.SUMMARY: There is a significant need to redefine HDL and its benefit. HDL transports a diverse set of functional proteins, including many binding proteins. HDL transports and deliver vitamins, carotenoids, and other small molecules. Moreover, HDL transports hormones, steroids and bile acids, and can modulate multiple endocrine pathways. HDLs also transport and deliver microRNAs to recipient cells and control gene expression. Likewise, HDLs carry bioactive lipids and can activate signaling cascades and receptors that control endothelial apoptosis, migration, survival and activation. Many of HDL’s alternative noncholesterol cargo likely confer many of HDL’s alternative functions.KEYWORDS: HDL, ApoA1, RCT, ABCA1, ABCG1, miRNA, HDL lipidome, HDL proteome